2007
DOI: 10.1007/s10826-006-9103-4
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Participation among Children with Conduct Problems and the Role of Telephone Reminders

Abstract: Children with antisocial, aggressive and disruptive behaviour problems are among the most frequent referrals to mental health services. These young people and their families present with a range of adverse contextual factors and can prove challenging to engage. We examined the characteristics of children with conduct problems, treatment participation, and the impact of telephone reminder calls. Consecutive referrals (N = 262) to two child and youth mental health services were randomly assigned to either a remi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…Seven RCTs 57,58,66,72,80,82,90 employed telephone reminders and followed a similarly standardised protocol consisting of up to three attempts to contact the patient before deeming the participant as uncontactable; if there was an answer machine or another person answered the telephone call, no message was left. Three RCTs 58,72,90 provided no information about contact rates; however, four of the RCTs 57,66,80,82 did provide relevant data indicating that between 0% and 58% of patients allocated to receive an appointment reminder by telephone could not be contacted. Roberts et al 82 randomly allocated 504 patients to receive either a telephone reminder or usual care to investigate the impact on attendance at respiratory outpatient clinics in the English NHS.…”
Section: Telephone Remindersmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven RCTs 57,58,66,72,80,82,90 employed telephone reminders and followed a similarly standardised protocol consisting of up to three attempts to contact the patient before deeming the participant as uncontactable; if there was an answer machine or another person answered the telephone call, no message was left. Three RCTs 58,72,90 provided no information about contact rates; however, four of the RCTs 57,66,80,82 did provide relevant data indicating that between 0% and 58% of patients allocated to receive an appointment reminder by telephone could not be contacted. Roberts et al 82 randomly allocated 504 patients to receive either a telephone reminder or usual care to investigate the impact on attendance at respiratory outpatient clinics in the English NHS.…”
Section: Telephone Remindersmentioning
confidence: 99%
“…25 In our review, all the RCTs that reported procedures for making telephone contact attempted to contact patients within usual working hours (09.00-17.00 hours) during the working week (Monday to Friday) in a 1-7 day window prior to the clinic appointment. 57,66,80,82,90,179 Many other reasons have also been frequently reported that further explain why patients may not be contactable using a telephone reminder system, e.g. the patient either did not have a telephone or had been disconnected, the patient never answers the telephone or the contact number provided was incorrect.…”
Section: Accessibilitymentioning
confidence: 99%
“…For example, the Health Belief Model (HBM, Rosenstock 1974) informed the interventions developed in a number of studies (e.g. Sawyer et al 2002;Watt et al, 2007;Donohue et al 1998;and McKay et al 1996a). The HBM proposes that health behavior depends on both an individual's perceptions of his/her vulnerability to an illness and his/her judgment of the perceived potential risk, barriers, or effectiveness of treatment (Elder et al 1999).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16] Studies in primary care and specialty clinics have demonstrated that staff phone calls are an effective intervention for reducing no-shows. [17][18][19][20][21][22][23][24][25][26][27][28][29][30] However, this convincing work is difficult to apply, because staff phone calls are timeconsuming and costly. Moreover, while this intervention is thought to be cost effective in clinics with high baseline noshow rates, the efficacy is less clear when baseline no-show rates are low.…”
Section: Introductionmentioning
confidence: 99%
“…18,19,30,31 Nevertheless, even in practices with low baseline no-show rates, the risk of no-show is heterogeneous-that is, some patients are more likely of noshows than others. 9,10,28,29,[32][33][34] Prior work has effectively demonstrated that no-shows are predictable; validated models can accurately predict the likelihood that a patient will fail to keep a scheduled appointment. 9,[35][36][37][38] Subspecialty clinics have made use of the predictability of no-shows by integrating predictive modeling to target interventions to those at high risk of no-show.…”
Section: Introductionmentioning
confidence: 99%